MCM9 deficiency impairs DNA damage repair during spermatogenesis, leading to Sertoli cell-only syndrome in humans - Xuan Sha; Xin Zhang; Hao Geng; Yuqian Li; Xun Xia; Guotong Li; Rong Hua; Kuokuo Li; Yang Gao; Qunshan Shen; Rui Guo; Yuping Xu; et al. (Cell Death Discovery)
Abstract Non-obstructive azoospermia (NOA) represents the most severe form of male infertility; however, its genetic etiology remains largely elusive. MCM9 is crucial for DNA damage repair in mammalian somatic cells, playing a key role in regulating both homologous recombination (HR) and mismatch repair (MMR) pathways. In mice, MCM9 deficiency leads to spermatogenic failure characterized by progressive germ cell depletion and impaired HR repair. However, the underlying mechanism remains unclear in humans. Our study identified two novel homozygous loss-of-function (LoF) mutations in MCM9 in two unrelated NOA patients presenting with Sertoli cell-only syndrome (SCOS). The absence of testicular MCM9 confirmed the pathogenicity of these LoF mutations. Furthermore, diminished HR-mediated DNA repair capacity observed in HEK293T cells, either lacking MCM9 or overexpressing mutant MCM9 plasmids, highlighted the deleterious impact of these LoF mutations on HR repair. Additionally, the confirmed interaction between human testicular MCM9 and both MSH2 and MLH1, alongside findings that human MCM9 is predominantly expressed in spermatogonial stem cells and spermatogonia, provides compelling evidence for the involvement of the MCM9-mediated MMR pathway in maintaining genomic integrity and supporting the viability and proliferation of spermatogonia in humans. Given the poor outcomes of microdissection testicular sperm extraction (micro-TESE) observed in both probands, we propose that biallelic LoF mutations in MCM9 may serve as non-invasive molecular biomarkers for predicting micro-TESE failure. These findings enhance our understanding of the genetic basis of human NOA, particularly SCOS, and provide valuable insights for genetic counseling and fertility guidance tailored to these patients.